CARING EXPERIENCES OF NURSES AND ELDERLY HEMODIALYSIS PATIENTS : BASIS FOR MODULAR DEVELOPMENT ON PATIENT’S CARE AND EDUCATION - Maria Caroline L. Santos; Nemia D. Calimbas; Ronnell D. dela Rosa (Jurnal Ilmu Pendidikan dan Budaya, 2024)
This phenomenological research study unveiled the meaning of caring experience between the nurse and elderly patient in the hemodialysis treatment setting using Schoenhofer's research-as-praxis methodological process. Using this method, the researchers conducted a dialogue that involved the presence of both participants at the same time to explore on: (1) the experiences of both nurse and elderly hemodialysis patients while undergoing hemodialysis treatment; and (2) how the concerns of elderly HD patients being addressed. Data from the twelve (12) participants were analyzed using QDA Miner Lite, and thematic three-phase analysis was done. The experiences of elderly HD patients were thematically described as care in reminders and restrictions, center as community of support, importance of family care and support, and multifaceted approach to dialysis treatment. Likewise, the experiences of nurses were described as they care for their HD patients, such as heart as the core of care, exhausted but fulfilled, and patience in communicating with patients and relatives. From the explored experiences of both nurse- and patient-participants, four (4) themes were created that answered the concerns of elderly HD patients and these include: resistance and forgetfulness require collaborative and consistent support, financial cost of dialysis is a challenge, patients find comfort in the center’s community to combat fear and loneliness, and living up to patient’s confidence is a continuous challenge. Though findings revealed that elderly HD patients require constant reminder in restricting fluid and dietary intake, they still find nurse’s behavior as a genuine manifestation of care and discipline. Nurses, on the other hand, are aware that elderly HD patients are becoming resistant and forgetful, thus, they require more attention and special care. It can be concluded that the caring relationship that is built between the nurse- and patient-participants is comparable to that of a family. The researchers recommend collaborative efforts between the college and hemodialysis centers/institutions for the conceptualization of various programs that could help the hemodialysis patients such as: creation of modules, infographic materials like comics and leaflets, to basically explain the importance of adhering to treatment and fluid restriction and depict real-life scenarios in a hemodialysis setting. Likewise, a video collection of interviews of various HD patients on their real-life experiences as they share their own treatment journey, and spiritual and mental health programs thru seminars and talks, to motivate and further boost patient’s morale and spirit.